Studying the chromatic responses of AuNPs embedment into the opal photonic crystals using the alexa 594 fluorescent dye - Phong, Pham Hong; Ha, Vu Thi Thu (Vietnam Journal of Science and Technology, 2022)
In this study, the chromatic responses of opal photonic crystals (PhCs) based on SiO2 microspheres fabricated by self-assembly followed by coating polyethylene glycol diacrylate (PEGDA/SiO2) were investigated. In the presence of Alexa@594 fluorescent dye, the fluorescent intensity of PEGDA/SiO2 and PEGDA/SiO2-AuNPs was enhanced 2.2-fold and 3.0-fold, respectively, compared with that of the SiO2 sample. This was elucidated by investigating the reflection spectra. The obtained stopband clearly showed a red-shift of the PEGDA/SiO2 about 70 nm (at 623 nm) which could overlap the emission wavelength of the fluorescent dye (617 nm). Plasmon resonance was also achieved when this chromatic response became more significant with the embedment of AuNPs into PEGDA/SiO2. These obtained results indicated that the material prepared by self-assembly of microsphere SiO2 coated with PEGDA showed a chromatic response of a PhC. Specially, with the presence of AuNPs in PEGDA, this behavior of the PhC became more significant. A such material can be helpful and promissing for further modification to apply to the field of chromatically optical sensing.